Pengaruh Layanan Penguasaan Konten Teknik Mind Mapping Terhadap Aktivitas Belajar Siswa - Kusumawardana, Alfam (Universitas Negeri Semarang, 2017)
This research was conducted on the based on the phenomenon in 5th grade SDN Plalangan 04 Gunungpati which has a low learning activities based on the results of the analysis of DCM in 5th grade. The purpose of this research is to know the learning activities of students before and after the given mastery of content service mind mapping techniques and whether the mastery of content service mind mapping techniques effect on learning activities of students. This research is experimental research design used is one group pretest-posttest design. Pre and post test form questionnaire learning activities. The population is all of the 5th grade the amount of 34 students and sample using a sampling of saturated so that the number of subjects for research are all students of 5th grade. Test hypotheses using a t-test analysis test by comparing the results of a pretest and posttest, obtained result tcount = 16.477 > ttable = 2.042, which means Ha accepted and Ho rejected. The result showed that the learning activities of students before and after the given mastery of content service mind mapping techniques experience an increase of 18.69%